Beyond comparison: Brillouin microscopy and AFM-based indentation reveal divergent insights into the mechanical profile of the murine retina - Gutmann, Marcus; Salvador, Jana Bachir; Müller, Paul; Kim, Kyoohyun; Schicht, Martin; Aif, Serhii; Paulsen, Friedrich; Meinel, Lorenz; Guck, Jochen; Möllmert, Stephanie (JPhys Photonics, 2024)
Mechanical tissue properties increasingly serve as pivotal phenotypic characteristics that are subject to change during development or pathological progression. The quantification of such material properties often relies on physical contact between a load-applying probe and an exposed sample surface. For most tissues, meeting these requirements entails an invasive preparation, which poses the risk of yielding mechanical properties that do not portray the physiological state of a tissue within a functioning organism. Brillouin microscopy has emerged as a non-invasive, optical technique that enables the assessment of mechanical cell and tissue properties with high spatio-temporal resolution. In optically transparent specimens, it does not require animal sacrifice, tissue dissection or sectioning. However, the extent to which results obtained from Brillouin microscopy allow to infer conclusions about potential results obtained with a contact-based technique, and vice versa, is unclear. Sources for discrepancies include the varying characteristic temporal and spatial scales, the directionality of measurement, environmental factors, and mechanical moduli probed. In this work, we addressed those aspects by quantifying the mechanical properties of acutely dissected murine retinae using Brillouin microscopy and atomic force microscopy (AFM)-based indentation measurements. Our results show a distinct mechanical profile of the retinal layers with respect to the Brillouin frequency shift, the Brillouin linewidth and the apparent Young’s modulus. Contrary to previous reports, our findings do not support a simple correlative relationship between Brillouin frequency shift and apparent Young’s modulus. Additionally, the divergent sensitivities of Brillouin microscopy and AFM-indentation measurements to structural features, as visualized by transmission electron microscopy, to cross-linking or changes post mortem underscore the dangers of assuming interchangeability between the two methods. In conclusion, our study advocates for viewing Brillouin microscopy and AFM-based indentation measurements as complementary tools, discouraging direct comparisons a priori and suggesting their combined use for a more comprehensive understanding of tissue mechanical properties.
Created from Fastlane, Scopus look-up
Keywords: central nervous system; genipin; mechanical properties; tissue mechanics